2015
DOI: 10.17795/jjnpp-20081
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Aflatoxin M1 in Raw Milk of Fariman City, Khorasan Province, Iran

Abstract: Background: Although milk is the valorous source of nutrition, consumption of aflatoxin M1 (AFM1) contaminated milk induces problems to human health. AFM1 is found in milk when dairy animals are fed with AFB1-contaminated feedstuff. AFM1 remains stable during milk pasteurization and storage as well as during the preparation of various dairy products. Objectives:The aim of the current study was to evaluate AFM1 contamination in raw milk of Fariman city. Materials and Methods: During the summer (July to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The same results were observed in Kamkar et al’s (2008) study on 52 ultra-high temperature (UHT) pasteurized milk samples, all of which showed AFM1 contamination ( 38 ). Zanjani et al (2015) reported that the mean AFM1 concentration in 45° raw milk samples was 11.61 ± 0.72 ng/L (range 6.3 - 23.3 ng/L) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…The same results were observed in Kamkar et al’s (2008) study on 52 ultra-high temperature (UHT) pasteurized milk samples, all of which showed AFM1 contamination ( 38 ). Zanjani et al (2015) reported that the mean AFM1 concentration in 45° raw milk samples was 11.61 ± 0.72 ng/L (range 6.3 - 23.3 ng/L) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…can easily grow in feedstuffs having humidity between 13% and 18%, and then they are able to produce aflatoxin in environmental humidity between 50% and 60%. For this reason, the level of AFM1 in feed in cool months is more than hot months 13 . In the present study, AFM1 was detected in 100% of the tested yoghurt samples by range from of 5-83ng/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Some physical treatment such as roasting, washing, and cooking was studied on the reduction of some mycotoxins in cereal and nut; these methods has reduced mycotoxin in food matrices [44][45][46][47][48][49][50][51][52][53][54].…”
Section: Control Of Mycotoxinsmentioning
confidence: 99%